74.7k views
0 votes
What is the 11th term in the sequence: an = -6n + 13?

User Nishantcm
by
5.4k points

2 Answers

2 votes


- 6(1) + 13 = 7 \\ - 6(2) + 13 = 1 \\ - 6(3) + 13 = - 5 \\ - 6(4) + 13 = - 11 \\ - 6(5) + 13 = - 17 \\ - 6(6) + 13 = - 23 \\ - 6(7) + 13 = - 29 \\ - 6(8) + 13 = - 35 \\ - 6(9) + 13 = - 41 \\ - 6(10) + 13 = - 47 \\ - 6(11) + 13 = - 53
The amswer is -53
User Bricelam
by
6.1k points
1 vote
Plug in n = 11. Then use the order of operations to simplify

an = -6n + 13
an = -6*n + 13
a11 = -6*11 + 13 ... every n is replaced with 11
a11 = -66 + 13
a11 = -53

Answer: -53

Note: this is an arithmetic sequence with first term 7 and common difference -6
User Niitaku
by
6.2k points